Stock Market Trend Prediction using Technical Indicators and Deep Learning Methods - Sarkar, Shreshtha; Nehal, Inteshab (International Journal of Computer Sciences and Engineering, 2021)
The stock market is volatile and is subject to fluctuations. There are many factors like news, fundamental indicators, and heuristic technical indicators et cetera which contribute to such fluctuations. The randomness and volatility have drawn the attention of many researchers and perplexed them. Algorithm trading has been gaining popularity, as machines are able to process tons of data. The ability of an algorithm to predict the price movement gives an opportunity to gain a fortune from the stock market. In this paper, we study the historical prices, calculate the technical indicators based on them, apply feature selection to remove multicollinearity and find the most important features affecting the prices before processing it into the LSTM network to predict the price movement. The prediction of market value can help maximize the profit while keeping the risk comparatively low.